Квантово-розмірний ефект напівпровідникових матеріалів - Шмидт, И. О.; Грицунов, А. В. (ХНУРЕ, 2018)
This report explains the quantum-size effect in semiconductor materialsand describes the energy of the particle size quantization.
Keywords: Квантово-розмірний ефект; напівпровідникові матеріали